Graphitic nanoparticles functionalized with epoxy moiety for enhancing the mechanical performance of hybrid carbon fiber reinforced polymer laminated composites. Issue 2 (3rd November 2020) - Khan, Nazrul Islam; Halder, Sudipta; Das, Subhankar; Goyat, Manjeet S.
Abstract: Exceptional properties and unique structural features of graphene make it a successful secondary reinforcing agent for the enhancement of mechanical performance of hybrid carbon fiber reinforced polymer (CFRP) composites. In this study, graphitic nanoparticles (GrNPs) were functionalized with the epoxy moieties through the traditional silanization method and an innovative approach of grafting with epichlorohydrin and then reinforced in epoxy system to prepare nanocomposites and hybrid CFRP laminated composites. The morphological, structural, and thermal investigation revealed the successful functionalization of GrNPs. The tensile strengths of the nanocomposites were found significantly enhanced by 36% due to incorporation of silanized GrNPs and 30% due to incorporation of epichlorohydrin grafted GrNPs compared to the neat epoxy. The tensile strengths of the resulting CFRP composites reinforced with silanized and epichlorohydrin grafted GrNPs showed 37% and 36% improvements, respectively, as compared to the control sample. Comparing the results of silanized and epichlorohydrin grafted GrNPs nanocomposites, it has been found that silanization has better potential to improve the mechanical performance of the hybrid CFRP composites as compared to epichlorohydrin grafting. Abstract : This investigation suggests that the functionalization of graphitic nanoparticles with 3‐glycidoxypropyltrimethoxy silane (GPTMS) and epichlorohydrin help in the improvement of the mechanical properties of the nanocomposites and carbon fiber reinforced polymer composites. However, comparing these two functionalization methods, GPTMS functionalization is found more effective as compared to the epichlorohydrin functionalization.